2019
DOI: 10.3390/agronomy9050261
|View full text |Cite
|
Sign up to set email alerts
|

Wx Gene in Hordeum chilense: Chromosomal Location and Characterisation of the Allelic Variation in the Two Main Ecotypes of the Species

Abstract: Starch, as the main grain component, has great importance in wheat quality, with the ratio between the two formed polymers, amylose and amylopectin, determining the starch properties. Granule-bound starch synthase I (GBSSI), or waxy protein, encoded by the Wx gene is the sole enzyme responsible for amylose synthesis. The current study evaluated the variability in Wx genes in two representative lines of Hordeum chilense Roem. et Schult., a wild barley species that was used in the development of tritordeum (×Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Hordeum chilense shows a good degree of collinearity with H. vulgare ( Ávila et al, 2019a ) and, thus, with all the members of the Triticeae tribe ( Mayer et al, 2011 ). Indeed, the position of H. chilense genes identified using candidate gene approaches in previous works is in agreement with their position in other Triticeae species ( Atienza et al, 2007a ; Gil-Humanes et al, 2009 ; Rodríguez-Suárez and Atienza, 2012 ; Alvarez et al, 2019 ; Rodríguez-Suárez et al, 2020 ). Thus, these candidate genes in chromosome 7D were a good starting point for identifying the gene involved in lutein esterification in Hch genome.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Hordeum chilense shows a good degree of collinearity with H. vulgare ( Ávila et al, 2019a ) and, thus, with all the members of the Triticeae tribe ( Mayer et al, 2011 ). Indeed, the position of H. chilense genes identified using candidate gene approaches in previous works is in agreement with their position in other Triticeae species ( Atienza et al, 2007a ; Gil-Humanes et al, 2009 ; Rodríguez-Suárez and Atienza, 2012 ; Alvarez et al, 2019 ; Rodríguez-Suárez et al, 2020 ). Thus, these candidate genes in chromosome 7D were a good starting point for identifying the gene involved in lutein esterification in Hch genome.…”
Section: Discussionsupporting
confidence: 87%
“…Due to the high degree of genetic collinearity that H. chilense shows with Triticeae species ( Ávila et al, 2019a ), the set of candidate genes identified in chromosome 7D is also valid for chromosome 7Hch, since orthologs of these genes are likely present in chromosome 7Hch. Indeed, genetic studies have shown that orthologous genes for traits of interest are in equivalent positions in H. chilense compared to wheat and/or barley, for instance Psy1 ( Atienza et al, 2007a ), APETALA2-like ( Gil-Humanes et al, 2009 ), carotenoid biosynthesis pathway ( Rodríguez-Suárez and Atienza, 2012 ), Ppo ( Rodríguez-Suárez and Atienza, 2014 ), Wx ( Alvarez et al, 2019 ), and Rfm1 ( Rodríguez-Suárez et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Carotenoid content [31,44,45]; carotenoid esterification [45,46]; mildew and greenbug resistance [20]; waxy protein [47]…”
Section: Progress In Breeding For Agronomic Performancementioning
confidence: 99%
“…Hordeum chilense has been also used to evaluate the variability for the Wx gene that encodes a waxy protein (a granule-bound starch synthase I), responsible for amylose synthesis [2]. Authors have located this Wx gene on the long arm of 7H ch chromosome and have identified two different alleles of this gene in H. chilense.…”
Section: Chromosome Manipulation Within the Triticeae Tribementioning
confidence: 99%